Development of Mubtada and Khabar materials from Syarah Qathru an-Nadaa Wa Balli As-Shada book for teaching Nahwu at Islamic Boarding School Ashhabul Yamin Lasi Agam - AYA, NURHAYATI (BiCED Proceeding, 2024)
The problem faced by researchers in this article is the lack of students' ability to understand the Mubtada and Khabar material in the Kitab Syarah Qathru an-Nadaa Wa Balli As-Shada, the lack of students' ability to identify Mubatada and khabar in Arabic texts, and the lack of students' desire to learn mubatada and khabar using the book Syarah Qathru an-Nadaa Wa Balli As-Shada. The purpose of the research in this article is to develop the material of mubtada and khabar in the book of Syarah Qathru an-Nadaa Wa Balli As-Shada for learning Nahwu science at Pondok Pesantren Ashhabul Yamin Lasi Agam. The research method used in this article is development and the research tools used are questionnaires, observation, interviews and documentation. Researchers chose the ADDIE method, which consists of five stages: analysis, design, development, implementation, and evaluation. The researcher obtained the conclusion that this product is feasible to use in teaching Nahwu science about Mubtada and Khabar. This conclusion is based on the questionnaire results from the experts and from the students during the 90% implementation. On a five-point scale, these results fall into the “excellent” scale. This product is suitable for use in learning mubtada and Khabar.